2011
DOI: 10.1007/s00420-010-0607-2
|View full text |Cite
|
Sign up to set email alerts
|

Health disparities between immigrant and Danish cleaners

Abstract: Although the health of the cleaners was alarmingly poor, the immigrant cleaners generally had a poorer self-reported health and work ability than the Danish cleaners. These findings highlight the need for occupational health actions among cleaners, particularly tailored to the immigrant subpopulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 49 publications
2
26
1
2
Order By: Relevance
“…Workers with high levels of occupational physical activity often have a low cardiorespiratory fitness (4,(24)(25)(26) and limited ability for pauses and restitution, which may result in an increased risk of overloading and impairing the cardiovascular system (22). Thus, an aerobic exercise intervention may affect factors for cardiovascular disease both positively and negatively.…”
Section: Korshøj Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Workers with high levels of occupational physical activity often have a low cardiorespiratory fitness (4,(24)(25)(26) and limited ability for pauses and restitution, which may result in an increased risk of overloading and impairing the cardiovascular system (22). Thus, an aerobic exercise intervention may affect factors for cardiovascular disease both positively and negatively.…”
Section: Korshøj Et Almentioning
confidence: 99%
“…Cleaners' cardiorespiratory fitness has been described as relatively low and consequently a high relative aerobic workload is expected (4,28). Moreover, a high prevalence of other cardiovascular risk factors including hypertension and obesity (25,29), and an overall elevated CVD risk have been reported among cleaners (30,31). Classical interventions have aimed to lower the relative aerobic workload among cleaners through the ergonomic improvement of tools (32)(33)(34).…”
Section: Korshøj Et Almentioning
confidence: 99%
“…All seven variables which associated significantly with neck pain in bivariate analysis by using Chi square test entered in the logistic regression. The significant predictors of neck pain in this model after control of confounders were (30)(31)(32)(33)(34)(35)(36)(37)(38)(39) and (40)(41)(42)(43)(44)(45)(46)(47)(48)(49) …”
Section: Multivariate Analysismentioning
confidence: 96%
“…In bivariate; Chi square analysis, the result of present study indicated that there were seven factors significantly associated with neck pain i.e. age, BMI, physical exercises, night shifts, neck bending, prolonged working hours on computer and personnel shortage.Further analysis, by using multiple logistic regression showed that age groups [30][31][32][33][34][35][36][37][38][39]) and [40][41][42][43][44][45][46][47][48][49] physical exercises (p= 0.025,, working time on computer (p= 0.029, night shifts (p= 0.001, personnel shortage (p= 0.005, and neck bending (p= 0.013, …”
mentioning
confidence: 99%
“…MSDs have been extensively studied in several countries; however, few studies have been carried out so as to investigate the relationship between MSDs and ethnicity [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%